Training on the Utilization of E-Commerce Technology and Product Design for Processed Mangrove Products at LKP Walidayna - Ridha Muldina Negara; Rohmat Tulloh; Sri Astuti; Ratna Mayasari; Pramitha Aulia; Nadya Moeliono (Faculty of Smart Technology and Engineering, Universitas Kristen Maranatha, Bandung, Indonesia, 2024)
The coastal area of Medan Marelan District in Medan City, North Sumatra Province, has extensive mangrove forests that have not been fully utilized. LKP Walidayna supports the empowerment program for productive communities in the coastal areas of Medan City. Currently, LKP Walidayna has provided training on processing mangrove fruits to the community, turning them into various processed food products such as Mangrove Pudding, Mangrove Syrup, Mangrove Jam, and Mangrove Dodol. The vocational training institution (LKP) is one form of non-formal education that communities can utilize to enhance quality, skills, and productivity. However, LKP Walidayna faces limitations, including the lack of effective information media to market its products more widely. Therefore, the proposed solution is the creation of a website and e-commerce platform to promote LKP Walidayna's mangrove products using effective and attractive marketing techniques. The e-commerce platform would contain information about activities, especially the processing of mangrove products. Based on feedback from participants in the product design and marketing strategy training for processed mangrove products through the website, it is concluded that the conducted training activities align with the needs of LKP Walidayna. LKP Walidayna expressed satisfaction with the visually appealing and user-friendly website.